Case Study on the Relationship between Leadership Profiles and Company Performance in Central African Republic - Bheem, Rajendrakumar; Amrita, Jinashree Muni (Journal of Global Economy, Business and Finance, 2025)
The main objective of this work aims to verify the existence of a link between the profile of the leader and the overall performance within companies in the Central African Republic and particularly in Bangui. The verification of this link was made and validated with companies in Bangui through linear regression analysis. The results show a positive and significant link between the profile of the leader and the overall performance of the company in our context.